2016
DOI: 10.1007/s00464-016-5322-y
|View full text |Cite
|
Sign up to set email alerts
|

Transoral endoscopic thyroidectomy vestibular approach with intraoperative nerve monitoring

Abstract: TOETVA is safe and feasible and provides an excellent cosmetic outcome with the most confidentially compared to the other remote access endoscopic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 0 publications
2
44
0
1
Order By: Relevance
“…Despite the rate being very low in the present day due to a better operative technique (40,41), it is better to avoid this problem. Inabnet et al (34), Dionigi et al (36), and Wang et al (33) demonstrated intraoperative neuromonitoring in TOETVA operations with good results. However, the numbers of patients in those papers were too small; larger studies should be conducted to confirm that neuromonitoring can reduce the rate of RLN injury.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the rate being very low in the present day due to a better operative technique (40,41), it is better to avoid this problem. Inabnet et al (34), Dionigi et al (36), and Wang et al (33) demonstrated intraoperative neuromonitoring in TOETVA operations with good results. However, the numbers of patients in those papers were too small; larger studies should be conducted to confirm that neuromonitoring can reduce the rate of RLN injury.…”
Section: Discussionmentioning
confidence: 97%
“…Indications for TOETVA are as follows: a predicted gland width on diagnostic imaging ≤10 cm; a thyroid volume outline of <45 mL or dominant nodule dimension of ≤50 mm; Bethesda category 3 or 4 lesions; primary papillary microcarcinoma without local or distant metastasis; patient request for optimal aesthetic results (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Exclusion criteria are as follows: patients unfit for Brief Report on Thyroid Surgery Monitored transoral endoscopic thyroidectomy via long monopolar stimulation probe general anesthesia; precedent radiation in the head, neck, or upper mediastinum; antecedent neck surgery; recurrent goiter; a gland volume of >45 mL or main nodule diameter of >50 mm; documentation of lymph node or distant metastases, tracheal/esophageal infiltration, preoperative laryngeal nerve palsy, hyperthyroidism, mediastinal goiter, or oral abscesses.…”
Section: Patient Selection and Workupmentioning
confidence: 99%
“…Exclusion criteria are as follows: patients unfit for Brief Report on Thyroid Surgery Monitored transoral endoscopic thyroidectomy via long monopolar stimulation probe general anesthesia; precedent radiation in the head, neck, or upper mediastinum; antecedent neck surgery; recurrent goiter; a gland volume of >45 mL or main nodule diameter of >50 mm; documentation of lymph node or distant metastases, tracheal/esophageal infiltration, preoperative laryngeal nerve palsy, hyperthyroidism, mediastinal goiter, or oral abscesses. Moreover, patients with poorly-or undifferentiated cancer, dorsal extrathyroidal radius, and/or lateral neck metastasis (N1b) are not favored for TOETVA (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Patient Selection and Workupmentioning
confidence: 99%
“…Hydrodissection is first performed with a 30 mL solution of 1 mg adrenaline diluted with 500 mL normal saline injected sub-platysma into the oral vestibular area of the lower lip down to the anterior neck and central working space (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Operative Techniquementioning
confidence: 99%
“…Contralateral thyroidectomy is accomplished only if the RLN EMG signal of first side is preserved (1)(2)(3)(4)(5)(6)(7)(8)(9). If surgical drain is required, this is placed by adding a 5-mm incision into the axilla and tunnelled up to neck; correct placement of drain is guarantee by endoscopic view.…”
Section: Operative Techniquementioning
confidence: 99%